-(-6x+2)=-3(1-2x)-8x

Simple and best practice solution for -(-6x+2)=-3(1-2x)-8x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(-6x+2)=-3(1-2x)-8x equation:


Simplifying
-1(-6x + 2) = -3(1 + -2x) + -8x

Reorder the terms:
-1(2 + -6x) = -3(1 + -2x) + -8x
(2 * -1 + -6x * -1) = -3(1 + -2x) + -8x
(-2 + 6x) = -3(1 + -2x) + -8x
-2 + 6x = (1 * -3 + -2x * -3) + -8x
-2 + 6x = (-3 + 6x) + -8x

Combine like terms: 6x + -8x = -2x
-2 + 6x = -3 + -2x

Solving
-2 + 6x = -3 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
-2 + 6x + 2x = -3 + -2x + 2x

Combine like terms: 6x + 2x = 8x
-2 + 8x = -3 + -2x + 2x

Combine like terms: -2x + 2x = 0
-2 + 8x = -3 + 0
-2 + 8x = -3

Add '2' to each side of the equation.
-2 + 2 + 8x = -3 + 2

Combine like terms: -2 + 2 = 0
0 + 8x = -3 + 2
8x = -3 + 2

Combine like terms: -3 + 2 = -1
8x = -1

Divide each side by '8'.
x = -0.125

Simplifying
x = -0.125

See similar equations:

| 2=2q-(5q+3) | | y^2+y+56=0 | | 4p-p-p-p-p-p-p+2p= | | x+60=4x | | 13v-8v-13=0 | | 10=-5(3+3r)-6r | | 7(3x+1)=28 | | 9+4x=-2x+21 | | 5x+97=11x-5 | | 123-6x=21x+18 | | y^2-10y+12=0 | | 6r+11=89 | | -.11x-6=-1 | | 7t+53=14+6t | | x^2-4x+140=0 | | 2x-5=2x-6 | | 9-12x-x^2=0 | | (2x+5)(6x+4)= | | 3x-x=10x-66 | | 47=2x+7x-7 | | (7p+5q)(-2p+6q)= | | -2+4x=14 | | 0=z^2-6z+5 | | 6x+102=15x-6 | | -2x+6y=15 | | -2p=40 | | 18-3u=9 | | 66=7 | | 7+3x=8(3+x) | | -7x+2=-5 | | 5x^2-9x-89= | | 20+x=25 |

Equations solver categories